E-110 Endovascular treatment decision in acute stroke: does physician sex matter? insights from an international multidisciplinary survey. (22nd July 2019) - Ospel, J; Kashani, N; Campbell, B; Foss, M; Turjman, F; Yoshimura, S; Wilson, A; Kunz, W; Cherian, M; Kim, B; Rabinstein, A; Fischer, U; et al.
Abstract : Introduction: Numerous studies have compared treatment approaches of female and male physicians in different medical subspecialties, some of them revealed significant differences. To date, only few women are engaged in the neurointerventional field. Hence, it is unclear whether the treatment practice is influenced by physicians' sex. We explored whether there are differences in treatment decisions made by female and male physicians. Materials and methods: An international cross-sectional survey of both female and male stroke physicians and neurointerventionalists was conducted. Participants were randomly assigned 10 cases out of a pool of 22 case scenarios and asked how they would treat the patient A) assumed there were no economical or infrastructural constraints, and B) given their current working conditions. Subgroup analyses were performed for female and male physicians respectively. Results: 607 physicians (97 women, 508 men, 2 who did not disclose their sex), of different specialties (326 neurologists, 173 interventional neuroradiologists, 81 interventional neurosurgeons, 2 geriatricians, 5 internists, 20 other) from 38 countries participated in this survey. 6070 responses were obtained. Neurologists constituted the largest group of both female (76.3%) and male (49.2%) physicians, with a more even distribution of specialties in male physicians. Assuming ideal conditions, no significant differences in EVT decision making was observed (EVT was favored by 77% of female and 79.3% of male physicians). Under their current working conditions, female physicians decided less frequently in favor of EVT (69.1%) as compared to their male colleagues (76.9%, p<0.001). Conclusion: Under the ideal conditions, EVT decision between male and female physicians did not differ. Current working conditions restricted female physicians' endovascular treatment decision to a greater degree as compared to their male colleagues, resulting in a significantly lower decision rate in favor of EVT. Disclosures: J. Ospel: None. N. Kashani: None. B. Campbell: None. M. Foss: None. F. Turjman: None. S. Yoshimura: None. A. Wilson: None. W. Kunz: None. M. Cherian: None. B. Kim: None. A. Rabinstein: None. U. Fischer: None. P. Sylaja: None. B. Baxter: None. J. Heo: None. B. Menon: None. G. Saposnik: None. M. Hill: None. M. Goyal: None. M. Almekhlafi: 1; C; unrestricted research grant by Stryker to University of Calgary.